Strength prediction of adhesively bonded single lap joints with different bondline thicknesses: A critical longitudinal strain approach. (15th March 2017) - Akhavan-Safar, A.; Ayatollahi, M.R.; da Silva, L.F.M.
Abstract: The effect of bondline thickness on the strength of adhesively bonded single lap joints (SLJs) is still an open issue. According to the analytical methods and also finite element (FE) results, increasing the adhesive thickness causes a more uniform stress and strain distribution along the adhesive layer and consequently leads to higher strength of the SLJs, while the experimental data has shown lower strength for joints with thicker bondlines. This paper deals with the effect of the adhesive thickness on the strength of SLJs from the perspective of the longitudinal strain along the adhesive mid-plane. The longitudinal strain is a recently proposed failure parameter which should be measured along the adhesive mid-plane, at a specific distance away from the joint bonding end. The FE results showed that under a constant tensile load, the values of longitudinal strain along the adhesive mid-plane, increase with adhesive thickness. It could be concluded that the introduced failure parameter could take into account the decrease in joint strength due to an increase in bondline thickness. Some experiments on SLJs with different adhesive thicknesses and bonding lengths were conducted to validate the method. Good correlation between the experimental results and the predictions were seen. The method was also applied on experimental results published by other researchers. The results again showed that the new strain based method could well consider the strength reduction of SLJs due to increasing adhesive thickness.